Incorporating Informal Digital Learning of English (IDLE) in The Speaking Classroom: Student’s Perception and Its Impact on Speaking Ability - Mukrim, Mukrim; Mertosono, Sudarkam; Marhum, Mochtar; Kamaruddin, Abdul (ICONELT, 2024)
Studies have demonstrated that engagement in IDLE activities enhances students’ English proficiency. However, incorporating IDLE in the classroom is still under-studied in the ELT area. Addressing the research gap, the study explores the perception of university students who enrolled in a speaking course on IDLE incorporation in the classroom and its impact on their speaking ability. A qualitative case study design was used to uncover this issue by inviting 17 first-year English Department students enrolled in a speaking course and involved in integrating IDLE with classroom activities for 7 weeks to participate in this study. Data were collected through focus group interviews, observation, and gaining documents, and analyzed using thematic analysis. The study shows that the students perceive the IDLE integration as enjoyable, increases willingness to communicate, promotes peer sharing and learning, and encourages students to engage with English content on social media. Additionally, IDLE integration develops students’ vocabulary, pronunciation, and listening skills, which enhance students’ speaking ability. This study suggests that the incorporation of IDLE in the classroom has a potent impact on improving English speaking proficiency.